„Kelet-Afrika kereskedő hercegei” - Tarrósy, István (Afrika Tanulmányok / Hungarian Journal of African Studies, 2010)
Tarrósy István a következő művet mutatta be: Oonk, Gijsbert (2009): The Karimjee Jivanjee Family. Merchant Princes of East Africa. 1800–2000. Amsterdam: Pallas Publications– Amsterdam University Press.